AKUNTANSI BAGI USAHA KECIL MENENGAH (SURVEI PADA UKM DI NTB) - Baiq Anggun Hilendri Lestari; Lalu Takdir Jumaidi; D. Tialurra Della Nabila (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the understanding of Small and Medium Enterprises (SMEs) owners in West Nusa Tenggara about accounting by looking at what their financial management looks like. Is it limited to bookkeeping or the preparation of financial statements. In addition, this study aims to determine the accounting information needs of SME owners in order to manage their business finances properly. Based on the results of the study, it can be explained that in general SMEs in West Nusa Tenggara do not understand accounting. The owners of SMEs feel that they do not need accounting because accounting is difficult and complicated. This research contributes to the owners of SMEs in West Nusa Tenggara by providing an understanding that the application of accounting is important in managing their business finances.